2017
DOI: 10.3233/nre-161387
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of persistent vegetative state in patients with severe traumatic brain injury and its trend during the past four decades: A meta-analysis

Abstract: Abstract. BACKGROUND:Estimating the prevalence of persistent vegetative state (PVS) following severe traumatic brain injury (sTBI) and its change over time is important for the study of the disease. OBJECTIVE: To estimate the prevalence of PVS at six months after sTBI and its trend over the past four decades, and to explore the effect of demographic data, such as age and sex, on the prevalence of PVS. METHOD: Observational studies presenting the prevalence of PVS or the number of patients with PVS at six month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Recent large-scale observational studies reported that 42% of patients admitted to the intensive care unit (ICU) with TBI in China and 37% in Europe had a GCS ≤ 8 [ 1 , 3 ]. An estimated 0.63–7.33% of patients presenting in coma following severe TBI are in a vegetative state 6 months after injury, and the incidence various significantly between centres [ 4 , 5 ]. Failure to emerge from coma, or emergence into a disorder of consciousness, presents important management and ethical problems, raising questions about the appropriateness of continued clinical care, and sometimes triggering decisions about withdrawal of life supporting treatments (WLST) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent large-scale observational studies reported that 42% of patients admitted to the intensive care unit (ICU) with TBI in China and 37% in Europe had a GCS ≤ 8 [ 1 , 3 ]. An estimated 0.63–7.33% of patients presenting in coma following severe TBI are in a vegetative state 6 months after injury, and the incidence various significantly between centres [ 4 , 5 ]. Failure to emerge from coma, or emergence into a disorder of consciousness, presents important management and ethical problems, raising questions about the appropriateness of continued clinical care, and sometimes triggering decisions about withdrawal of life supporting treatments (WLST) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 The data were used as a rough check on the validity of the estimated figures. Table 1 shows the five review papers found: the first published in 1994, 25 two published in 2014, 30,31 a systematic review restricted to head injury, 32 and a narrative review. 29 These reviews reveal how few primary studies there are, especially of incidence, and the low the quality of most studies.…”
Section: Finally I Have Collected Papers On People Withmentioning
confidence: 99%
“…Studies on populations of people with traumatic brain injury suggest an incidence of 0.29-0.7/100,000/year at four weeks from this cause and that between 3% and 7% of all incident cases of severe brain injury are in a PDOC at six months. 32,48…”
Section: Incidencementioning
confidence: 99%
“…The prevalence varies according to the location and time. There is no consensus of the relationship of the age and sex of the patients with PVS, and its epidemiology is still unclear for many countries [1,[7][8][9]. This may be related to the misdiagnosis rate in these patients which is not rare [10][11][12], and for this reason, it might compromise clinical statistics, medical practice, and therapy approach.…”
Section: Introductionmentioning
confidence: 99%